The Constitutional Court, the regulation of usury and challengesto the constitutionality of the amendment made to the BCR'sOrganic Law by Law 31143 - Godos, Alix (2025)
In this article the authors analyze whether or not the amendment made to Article 52 of the Organic Law of the Central Reserve Bank, Decree Law N. 26123 by Law 31143, Law that protects consumers of financial services from usury, is constitutional or not, as a result of the Constitutional Court's Decision (Plenary. Decision 95/2024-).